The Effect of Hydroxychloroquine on Residual Proteinuria in Patients With Immunoglobulin A Nephropathy: A Retrospective Study Based on Propensity Score Matching - Liu, Mijia; Bian, Xueyan; Wang, Li; Li, Guisen (Frontiers in Medicine, 2022)
Background There is insufficient evidence to support the use of hydroxychloroquine (HCQ) in Immunoglobulin A nephropathy (IgAN) patients with high residual proteinuria in spite of 6-months supportive treatment combined with corticosteroids (P) and/or immunosuppressives (IM). This study aims to explore the effect of HCQ on residual proteinuria in IgAN. Methods This is a retrospective study. IgAN patients who had residual proteinuria ≥0.3 g/24h after 6-month treatment by renin-angiotensin system inhibitors (RASI) + P +/- IM were included. Groups were divided based on the different regimens and then matched by the propensity score matching method. The primary outcome was defined as the cumulative frequency of residual proteinuria reduction ≥30%. Results RASI (n=83), HCQ + RASI (n=52), RASI + P +/- IM (n=133) and HCQ + RASI + P +/- IM (n=38) groups were included. HCQ + RASI group had a higher level of residual proteinuria and a worse renal function than those in the RASI group. The renal function was worse in the HCQ + RASI + P +/- IM group than that in the control group, but residual proteinuria levels were similar. After matching, there were 33 patients in the first two groups and 26 patients in the latter two groups, respectively. The cumulative frequency of residual proteinuria reduction ≥30% in HCQ + RASI + P +/- IM group was higher than that in control group (88.5% vs. 61.5%, χ2= 6.168, p = 0.013). HCQ combination treatment and males were independent factors. Conclusion The addition of HCQ treatment can effectively reduce the residual proteinuria in IgAN patients with insufficient responses to supportive treatment combined with P and/or IM and the cumulative frequency of effective reduction of residual proteinuria can reach 88.5%.